Liver Fibrosis—From Mechanisms of Injury to Modulation of Disease - Liedtke, Christian; Nevzorova, Yulia A.; Luedde, Tom; Zimmermann, Henning; Kroy, Daniela; Strnad, Pavel; Berres, Marie-Luise; Bernhagen, Jürgen; Tacke, Frank; Nattermann, Jacob; Spengler, Ulrich; Sauerbruch, Tilman; et al. (Frontiers in Medicine, 2022)
The Transregional Collaborative Research Center “Organ Fibrosis: From Mechanisms of Injury to Modulation of Disease” (referred to as SFB/TRR57) was funded for 13 years (2009–2021) by the German Research Council (DFG). This consortium was hosted by the Medical Schools of the RWTH Aachen University and Bonn University in Germany. The SFB/TRR57 implemented combined basic and clinical research to achieve detailed knowledge in three selected key questions: (i) What are the relevant mechanisms and signal pathways required for initiating organ fibrosis? (ii) Which immunological mechanisms and molecules contribute to organ fibrosis? and (iii) How can organ fibrosis be modulated, e.g., by interventional strategies including imaging and pharmacological approaches? In this review we will summarize the liver-related key findings of this consortium gained within the last 12 years on these three aspects of liver fibrogenesis. We will highlight the role of cell death and cell cycle pathways as well as nutritional and iron-related mechanisms for liver fibrosis initiation. Moreover, we will define and characterize the major immune cell compartments relevant for liver fibrogenesis, and finally point to potential signaling pathways and pharmacological targets that turned out to be suitable to develop novel approaches for improved therapy and diagnosis of liver fibrosis. In summary, this review will provide a comprehensive overview about the knowledge on liver fibrogenesis and its potential therapy gained by the SFB/TRR57 consortium within the last decade. The kidney-related research results obtained by the same consortium are highlighted in an article published back-to-back in Frontiers in Medicine.